Study of soil rhizobacteria from Chernevaya Taiga in Western Siberia and their potential effect on plant growth - Kravchenko, Irina; Tikhonova, Ekaterina; Konopkin, Aleksey; Lapidus, Alla (Nexo Revista Científica, 2022)
The isolation of soil bacteria from various environments with exceptionally high fertility rates represents an opportunity to identify promising agents to promote agriculture production. The paper aims to study the densities of cultivable bacteria and isolate bacteria from the radish and spring wheat rhizosphere. Plants were grown in the pot experiment with virgin Chernevaya soil, which possessed extraordinary productivity, and zonal forest soil that did not demonstrate similar features. Fifty-nine bacterial isolates were purified and evaluated for their beneficial effects on the early growth of wheat. Isolates belonged to Proteobacteria, Actinobacteria, and Firmicutes phyla, and the most represented genera were Pseudomonas, Streptomyces, Paenibacillus, and Methylobacterium. These dominant bacteria were used in plant inoculation studies. Strains promoted a significant increase in shoot and root length and biomass, thus they may be considered plant growth-promoting rhizobacteria [PGPR]. Regarding biotest assays, strains that displayed high plant growth-promoting capabilities [PGP] were selected for further investigation. This study contributed to bacteria isolates from a unique natural environment with biotechnological potentials in improving plant growth and showed potency to be exploited as bioinoculants. El aislamiento de bacterias del suelo de varios ambientes con tasas de fertilidad excepcionalmente altas representa una oportunidad para identificar agentes prometedores para promover la producción agrícola. El artículo tiene como objetivo estudiar las densidades de las densidades bacterianas cultivables y aislar bacterias de la rizosfera de rábano y trigo de primavera. Las plantas se cultivaron en el experimento de la maceta con suelo virgen Chernevaya, que poseía una extraordinaria productividad, y suelo de bosque zonal que no mostraba características similares. Cincuenta y nueve aislados bacterianos fueron purificados y evaluados por sus efectos beneficiosos sobre el crecimiento temprano del trigo. Los ...